Intrinsic vs. extrinsic motivation in high school physical education: Which fuels adolescent achievement emotions better? - Mustafa Enes Işıkgöz (PLoS ONE, 2025)
The purpose of this study was to examine the relationship between the intrinsic, extrinsic, and amotivation levels of high school students toward physical education and their emotions of achievement. The study was carried out in the fall semester of the 2024-2025 academic year, with 1399 students studying at various high schools in Turkey. Participants' motivation levels were assessed using the "Motivation for Participation in Physical Education Lesson Scale," and their achievement emotions were evaluated with the "Achievement Emotions Scale for Physical Education." A cross-sectional design was used in the study and data were analysed using structural equation modelling. The findings showed intrinsic motivation strongly related to positive achievement emotions and negatively to negative ones. Extrinsic motivation was weakly correlated with positive achievement emotions and not significantly with negative ones. Amotivation negatively correlated with positive achievement emotions and positively correlated with negative ones. Students' motivation and emotions are influenced by how well their basic psychological needs are met, according to self-determination and psychological needs theories. The support of intrinsic motivation in physical education is essential for their achievement emotions and well-being. Teachers must promote autonomy, competence, and relatedness in learning environments. Future studies should test these findings in various cultural contexts using various data sources and longitudinal designs. Exploring technological and cultural influences on motivation will add valuable information to the literature.